Harm avoidance and childhood adversities in patients with obsessive–compulsive disorder and their unaffected first‐degree relatives. (3rd February 2017) - Bey, K.; Lennertz, L.; Riesel, A.; Klawohn, J.; Kaufmann, C.; Heinzel, S.; Grützmann, R.; Kathmann, N.; Wagner, M.
Abstract : Objective: The etiology of obsessive–compulsive disorder (OCD) is assumed to involve interactions between genetically determined vulnerability factors and significant environmental features. Here, we aim to investigate how the personality trait harm avoidance and the experience of childhood adversities contribute to OCD. Method: A total of 169 patients with OCD, 157 healthy comparison subjects, and 57 unaffected first‐degree relatives of patients with OCD participated in the study. Harm avoidance was assessed using the Temperament and Character Inventory, and the severity of childhood adversities was measured with the Childhood Trauma Questionnaire. Results: Both patients with OCD and relatives showed elevated levels of harm avoidance compared to controls. Furthermore, patients exhibited significantly higher scores than relatives. This linear pattern was observed throughout all subscales of harm avoidance, and remained stable after controlling for the severity of depressive and obsessive–compulsive symptoms. With regard to childhood adversities, patients with OCD reported higher levels than relatives and controls. Conclusion: Our results provide further evidence for a diathesis‐stress model of OCD. While patients and unaffected relatives share elevated levels of harm avoidance, supporting the role of harm avoidance as an endophenotype of OCD, a heightened severity of childhood adversity was only observed in patients. The assumed biological underpinnings of these findings are discussed.